Reasons for a medicine for needy populations - Ibiapina Ferreira Costa, Sergio (O Mundo da Saúde, 2007)
Bioethics has as a current challenge to give grounds for using or not a medicine for needy populations. The reasons that cause the use of arguments that justify the criteria of fairness and justice become indispensable if one intends to know the population segments that are devoid of the minimum consumption goods. Health is part of these goods, for excluded persons hardly ever have access to it when necessary. Health, as one of the values that is part of human rights, cannot be separated from the other values such as life, freedom, autonomy and respect for the dignity of the person. Medicine offered to needy populations not always has the obligation of being endowed with a greater technological wealth. This part of the population deserves more information, by means of a reasonable education, than the use of examinations or prescriptions of drugs. The structural problems that cause injustice must be equated and deserve more attention from the State regarding the universalization of the access to health systems, when it is necessary. This distortion will only be corrected by means of fairness and justice complemented by income distribution to the need populations.